Estudo do potencial de biossorção da Moringa oleifera Lam na remoção de atrazina em amostras aquosas utilizando leito fixo - Homem, Natália Cândido (2016)
Atrazine (ATZ; 2-chloro-4-ethylamino-6-isopropylamino-s triazine) is one of the most widely used herbicide in the world. However, studies have shown that its use can cause environmental problems, such as surface and ground water contamination, and in humans, can cause problems in reproductive and developmental systems. Hence, ATZ was included in the priority substances list of the United States Environmental Protection Agency (US EPA) and European Comission (EC). Thus, suitable treatment methods need to be developed aiming the removal of this herbicide from contaminated water. Adsorption is one of the most used methods to treat water containing organic compounds, and many studies have been conducted in order to obtain adsorbents with low cost and high availability, like agricultural sources biomass, biological, and industrial by-products. The plant parts of Moringa oleifera Lam (MO) have been used as coagulating agents for water treatment and as biosorbents. The MO seeds have demonstrated high efficiency in removal of many pollutants in aqueous solutions, such as metals and organic compounds. The seed husks are considered a by-product of its use. This way, this study evaluated the biosorption potential of ATZ by MO seed husks in fixed-bed column. The biosorbent was characterized by FT-IR spectra, scanning electron microscopy (SEM) and point of zero charge (pHpzc). The operating parameters influence in biosorption process was valued by breakthrough curves in which were evaluated the effect of bed height, flow rate, pH and inlet concentration. Higher ATZ sorption capacity of MO (0.314 mg g-1, with a removal percentage of 40%) was achieved at higher bed height, lower flow rate, higher inlet concentration and pH 7. The Adams-Bohart, Thomas and Yoon-Nelson models were used to predict the breakthrough curves, showing agreement with experimental data. Regeneration studies were performed and the biosorbent showed high efficiency of removal of ATZ for, at least, five cycles of biosorption-desorption. The results suggest that MO seed husks have potential as a promising biosorbent on ATZ removal in dynamic biosorption systems.